Les monuments de cailloux dans le paysage arctique - Hamelin, Louis-Édmond (Cahiers de géographie du Québec, 1956)
Stones and pebbles are everywhere in the Canadian Arctic ; it is an integrant part of its physical landscape. When these stones and pebbles are put together in one spot to form a monument, a cairn, a land mark, a tumulus, it is still more significant, it reveals the appearance of men in the country. Man is the principal cause among others of the inukshuks or cairns. The article deals with : 1. a classification according to shapes of the cairns : 2. a description of their main characteristics ; 3. an analysis of the responsible agents, especially men and its motives.